Risk Factors Associated with in Hospital Complication Post Gastrointestinal, Pancreatic, Hepatic Cancer Surgery: A Retrospective Case Control Study (RAPHA Study) - Nestor U Subong; Guntur Darmawan; David Raymund K Salvador; Margrette Ruth L Bernardo (The Indonesian Society for Digestive Endoscopy, 2018)
Background:This study aims todevelop a scoring system that will predict in-hospital morbidity post gastrointestinal (GI), pancreatic, hepatic cancer surgery in adult patients. This study took place in De La Salle University Medical Center.Method: Two hundred eighty five (285) adult patients 18 years old and above who underwent gastrointestinal, pancreatic and hepatic cancer surgery from 2010 to July 31, 2014 were included. Variables were evaluated in the univariate and multivariate analysis. Calculation of specific score from the resulting factors was performed by logistic regression analysis to develop the scoring system and to determine the best cut-off score in predicting in-hospital morbidity.Results: Out of 142 patients with post-operative complications, factors significantly associated with morbidity were as follows: age ≥ 75 years (p = 0.002), low serum albumin (p = 0.00), abnormal electrocardiogram (ECG) findings (p = 0.036) and emergency surgery (p = 0.000). Calculated best cut-off score was 1.4.Conclusion: The RAPHA scoring system may serve as a promising aid in predicting morbidity and mortality among patients who will undergo GI cancer surgery.